Introducing vigilant audiences - Trottier, Daniel; Gabdulhakov, Rashid; Huang, Qian (Open Book Publishers, 2020)
Intro -- Contents -- Acknowledgements -- Notes on Contributors -- Introducing Vigilant Audiences -- 'For the Greater Good?' Vigilantism in Online Pop Culture Fandoms -- Contesting the Vulgar Hanmai Performance from Kuaishou: Online Vigilantism toward Chinese Underclass Youths on Social Media Platforms -- 'I don't think that's very funny': Scrutiny of Comedy in the Digital Age -- Criticism of Moral Policing in Russia: Controversies around Lev Protiv in Moscow -- Far-Right Digital Vigilantism as Technical Mediation: Anti-Immigration Activism on YouTube